Exploring Ideology Represented in a Cover Book of an Indonesian ELT Textbook - Rahmi Hidayati; Sarah Aldina; Suci Indah Sari; Syifa Khairunnisa; Siti Ayuwandana Putri (Siliwangi University, 2021)
The textbook is one of kind in a variety of learning sources to support the learning process to add new information and knowledge to the readers. Every textbook usually contains a cover that describes the content of the textbook it is. In this research, the researcher investigates multimodality in a cover of textbook seventh grade Junior High School in Indonesia. In this research, the researchers focus on exploring the ideology used in that textbook. To examine the ideological representation, this study takes a multimodal social semiotic (MSS) approach conducted by Kress (2010). There are four points in the framework; Rhetor, design, ground, and interpreter. This research used qualitative as a method. Qualitative research is a method of social action that stresses the way people interpret their experiences to understand social reality (Mohajan, 2018). A case study is used as a research design. The case study research design has evolved over the past few years as a useful tool for investigating trends and specific situations in many scientific disciplines. From the result of finding and discussion, the researcher found ideologies in cover seventh grade Junior High School textbook in Indonesia such as the design of globe which held with the different skin tones of hands, that design represented unity in diversity it means even though we have a different background but we are one, we can communicate with people around the world using English as a communication tool. In a nutshell, the different skin tone of hand symbols in the English textbook seventh grade means that in this world, we can live in harmony with people from different identities with us. The ideology of the Bhinneka Tunggal Ika teaches us that every difference is beautiful. Since we are diverse we unite.